TO STUDY PATTERN OF DRUG RESISTANCE OF ANTITUBERCULAR THERAPY IN ALCOHOLIC LIVER DISEASE AND NON-ALCOHOLICS - Dr Gopika Sharma; Dr.O.P. Jatav; Dr.K P Ranjan (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction: Tuberculosis remains a global health threat, with drug resistance complicating its control. Alcohol use and alcoholic liver disease impair drug metabolism, immune defense, and treatment adherence, creating a higher risk of resistant TB. These factors highlight the need for integrated management addressing both addiction and comorbid liver dysfunction.Aim and Objective: This study aimed to assess the prevalence and pattern of antitubercular therapy (ATT) resistance in patients with and without ALD, and to evaluate the relationship between alcohol consumption, liver disease severity, and treatment outcomes.Materials and Methods: A prospective case–control observational study was conducted over 1.5 years at J.A. Group of Hospitals, Gwalior. Sixty adults (aged 30–60 years) with drug-resistant pulmonary TB, confirmed by CBNAAT, Line Probe Assay, and radiological findings, were included. Patients were stratified into two cohorts: 26 with ALD and 34 non-alcoholics. Clinical, microbiological, and radiological profiles were recorded, and drug resistance patterns were analyzed.Results: The cohort was predominantly male (73.3%) with a mean age of 42.7 years. All alcoholics were male. Course completion of ATT was lower in alcoholics (8.3%) compared to non-alcoholics (20%). CBNAAT revealed rifampicin resistance in 53.8% of alcoholics versus 23.5% in non-alcoholics, while MDR and XDR cases were more common among alcoholics. Longer duration and severity of alcohol use correlated with higher resistance, particularly RR-TB and XDR-TB.Conclusion: Alcohol misuse and ALD are strongly associated with poor treatment adherence and higher rates of drug-resistant TB. Integrating addiction management, liver care, and routine alcohol screening into TB programs is essential to improve adherence, reduce resistance, and achieve better outcomes.